Identification of human–carnivore conflict hotspots to prioritize mitigation efforts. Issue 24 (5th November 2017) - Broekhuis, Femke; Cushman, Samuel A.; Elliot, Nicholas B.
Abstract: Human–carnivore conflict is a primary driver of carnivore declines worldwide and resolving these conflicts is a conservation priority. However, resources to mitigate conflicts are limited and should be focused on areas of highest priority. We conducted 820 semistructured interviews with community members living within Kenya's Maasai Mara ecosystem. A multiscale analysis was used to determine the influence of husbandry and environmental factors on livestock depredation inside livestock enclosures (bomas). Areas with a high proportion of closed habitat and protected areas had the highest risk of depredation. Depredation was most likely to occur at weak bomas and at households where there were fewer dogs. We used the results to identify potential conflict hotspots by mapping the probability of livestock depredation across the landscape. 21.4% of the landscape was classified as high risk, and within these areas, 53.4% of the households that were interviewed had weak bomas. Synthesis and applications . With limited resources available to mitigate human–carnivore conflicts, it is imperative that areas are identified where livestock is most at risk of depredation. Focusing mitigation measures on high‐risk areas may reduce conflict and lead to a decrease in retaliatory killings of predators. Abstract : Human–carnivore conflict is a primary driver of carnivore declines worldwide, and resolving these conflicts is a conservation priority. Using reported depredation data from 820 semistructured interviews conducted in the Maasai Mara, Kenya, the influence of husbandry and environmental factors on livestock depredation inside livestock enclosures was determined. Both husbandry and environmental factors influenced whether a depredation event would occur and the results were used to identify potential conflict hotspots by mapping the probability of livestock depredation across the Mara landscape.